Laparoscopic procedure for rare liver’s round ligament cyst: A case report - Mai-Phan, Tuong-Anh; Nguyen, Dung Anh; Do, Thu-Phuong Thi; Nguyen, Tien-Dung Thanh; Tran, Tan Trong (Indian Journal of Case Reports, 2020)
Liver’s ligament cysts, especially uncommon and the liver’s round ligament cysts, have been sporadically presented in some case reports during the past decade. All reported cases were treated by laparotomy. This report discusses the case of asymptomatic liver’s round ligament cyst. The patient was hospitalized due to progressive epigastric pain for 1 week. Abdominal ultrasound and computed tomography scans showed a fluid density bulk in the pre-peritoneal space, suggestive of a cyst in the liver’s ligament. A laparoscopy was indicated to excise this cyst and the specimens were sent to a pathologist. The patient recovered uneventfully and discharged after 1 day of operation. In conclusion, exploratory laparoscopy and total resection of these lesions are necessary to exclude malignancy. Furthermore, laparoscopic round ligament cyst removal is applicable and it helps the patient with enhanced recovery.